2014
DOI: 10.1021/ol501175q
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder Reaction of 1,3-Diarylbenzo[c]furans with Thiophene S,S-Dioxide/Indenone Derivatives: A Facile Preparation of Substituted Dibenzothiophene S,S-Dioxides and Fluorenones

Abstract: One pot syntheses of substituted dibenzothiophene S,S-dioxides and fluorenones were successfully achieved by Diels-Alder reaction of benzo[c]furans with thiophene S,S-dioxides and indenones, respectively. Photophysical properties of representative seven- and nine-membered dibenzothiophene S,S-dioxide acenes were also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…reaction of 10a and 11a to give 12a (Scheme 9). 28 This reaction interestingly resulted in annulation of a naphthalene unit after acidic workup to synthesize π-extended benzonaphthothiophenes from readily available smaller π-systems. The aromatic metamorphosis of 12a resulted in the formation of benzocarbazole 13a easily.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…reaction of 10a and 11a to give 12a (Scheme 9). 28 This reaction interestingly resulted in annulation of a naphthalene unit after acidic workup to synthesize π-extended benzonaphthothiophenes from readily available smaller π-systems. The aromatic metamorphosis of 12a resulted in the formation of benzocarbazole 13a easily.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…Two approaches have been generally applied to synthesize arylsulfones: post-oxidization, where the sulfide-bridged system is first synthesized and then oxidized [6]; and the pre-oxidization, where benzothiophene S,S-dioxides are first synthesized and then coupled with other reactant to build larger sulfone-bridged structures [10,11]. For example, Nandakumar et al recently reported the synthesis of substituted dibenzothiophenes S,Sdioxides via a Diels-Alder reaction between 1,3-diarylbenzo[c] furans and thiophene S,S-dioxide derivatives [11].…”
Section: Synthesis and Structuresmentioning
confidence: 99%
“…For example, Nandakumar et al recently reported the synthesis of substituted dibenzothiophenes S,Sdioxides via a Diels-Alder reaction between 1,3-diarylbenzo[c] furans and thiophene S,S-dioxide derivatives [11]. We chose to synthesize PTAs via acid-induced cyclization reaction of aromatic methyl sulfoxides [9], then oxidize them by excess metachloroperoxybenzoic acid (mCPBA) to generate the sulfone compounds in high yield.…”
Section: Synthesis and Structuresmentioning
confidence: 99%
“…To realize this challenging goal, we adopted a strategy involving the incorporation of thio, sulfinyl, and sulfonyl groups into azaacenes. The sulfonyl groups are of particular importance, since they could efficiently reduce frontier energy levels . In the case of sulfinyl groups, they create a bridge from the thio to sulfonyl groups, which influences the fine‐tuning of energy level modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfonylg roups are of particular importance,s ince they could efficiently reduce frontier energy levels. [31][32][33] In the case of sulfinyl groups,t hey createabridge from the thio to sulfonyl groups,w hich influencest he finetuningo fe nergy level modulation. Herein we report as eries of sulfur-containing bent N-heteroacenes with different p-conjugated length,o ptical, and electricalp roperties ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%